2013
DOI: 10.1242/dev.077230
|View full text |Cite
|
Sign up to set email alerts
|

The elongation rate of RNA polymerase II in zebrafish and its significance in the somite segmentation clock

Abstract: SUMMARYA gene expression oscillator called the segmentation clock controls somite segmentation in the vertebrate embryo. In zebrafish, the oscillatory transcriptional repressor genes her1 and her7 are crucial for genesis of the oscillations, which are thought to arise from negative autoregulation of these genes. The period of oscillation is predicted to depend on delays in the negative-feedback loop, including, most importantly, the transcriptional delay -the time taken to make each molecule of her1 or her7 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 52 publications
4
86
0
Order By: Relevance
“…We and others have also reported that traveling wave-like expression patterns are significantly disturbed in her7 −/− mutants; there is also a large variation from embryo to embryo from the same mutant clutch (Choorapoikayil et al, 2012;Hanisch et al, 2013;Schroter et al, 2012). Our model nicely recapitulates this phenotype.…”
Section: −/−mentioning
confidence: 52%
See 3 more Smart Citations
“…We and others have also reported that traveling wave-like expression patterns are significantly disturbed in her7 −/− mutants; there is also a large variation from embryo to embryo from the same mutant clutch (Choorapoikayil et al, 2012;Hanisch et al, 2013;Schroter et al, 2012). Our model nicely recapitulates this phenotype.…”
Section: −/−mentioning
confidence: 52%
“…We and others have recently reported that her1 −/− embryos halt their oscillations earlier in the PSM and manifest only one or two expression waves at mid-somitogenesis stages; this results in the formation of one less stripe in the anterior PSM in her1 −/− mutants (Choorapoikayil et al, 2012;Hanisch et al, 2013) compared with wild-type, hes6 −/− and her7 −/− ;hes6 −/− embryos (Schroter et al, 2012). Our model reproduced this observation successfully (Fig.…”
Section: −/−mentioning
confidence: 85%
See 2 more Smart Citations
“…The her/hes genes form both hetero-and homodimers and negatively regulate their own transcription (Hirata et al 2002;Oates and Ho 2002;Bessho et al 2003;Giudicelli et al 2007;Brend and Holley 2009a;Schröter et al 2012;Trofka et al 2012;Hanisch et al 2013). Due to a short half-life, this negative feedback results in repeated cycles of expression and repression of the her/hes genes within the presomitic mesoderm (PSM), the frequency of which correlates with the rate of somite formation (Lewis 2003;Monk 2003;Hirata et al 2004;Ishii et al 2008;Schröter and Oates 2010;Takashima et al 2011;Delaune et al 2012;Ay et al 2013;Harima et al 2013).…”
mentioning
confidence: 99%